Fundamentals of Entrepreneurship (ENT300) : Eskac Paradise / Azzatul Natasha Ahmad … [et al.]. - Ahmad, Azzatul Natasha; Harmy, Nur Sabrina Natasha; Affandi, Dyg Afiqah Shafira (2019)
After making some research on the business opportunity available in Kota Samarahan area, we have decided to specify our business in providing the delicious “Ais Kacang". Our group come out business plan and our organization will be known as "Eskac Paradise which is located in The Summer Shopping Mall, Samarahan. Every member in the organization is actively participating in the business. We have reached a consensus regarding the organizational of our company and has been decided Azzatul Natasha Binti Ahmad is selected as the General and the Marketing Manager, while Dyg Afiqah Shafira Binti Afandi as Administrative and Operational Manager and for Financial Manager, Nur Sabrina Natasha Binti Harmy was selected.